Application of choline chloride deep eutectic solvents and high‐speed counter‐current chromatography to the extraction and purification of flavonoids from the thorns of Gleditsia sinensis Lam. Issue 4 (17th September 2020) - Yu, Jinqian; Zhao, Lei; Sun, Xiaowei; Sun, Chenglong; Wang, Xiao
Abstract: Introduction: Flavonoids are the most important and effective constituents in the thorns of Gleditsia sinensis Lam., which have been known to show antimicrobial, antiviral, anticancer, and anticoagulant activities. However, efficient extraction and separation methods for these flavonoids are not currently established. Objective: To develop an efficient method for efficient extraction and rapid separation of flavonoids from the thorns of G. sinensis using choline chloride deep eutectic solvents (DESs) and high‐speed counter‐current chromatography (HSCCC). Methodology: As for extraction, DES composed of choline chloride and 1, 4‐butanediol at 1:4 mole ratio, at an extraction temperature of 55°C, 20% of water content, 1:30 mg/mL for solid–liquid ratio, and 45 min for extraction time were selected as the optimised extraction method for flavonoids from the thorns of G. sinensis . As for separation, dichloromethane–methanol– n ‐butanol–water (4:3:0.5:2, v/v ) was applied to develop a successful strategy for purification of the flavonoids by HSCCC. Results: Totally, five flavonoids, including padmatin (1, 3.7 mg), isovitexin (2, 2.5 mg), 3′, 5, 5′, 7‐tetrahydroxyflavanonol (3, 11.2 mg), 7, 4′‐dihydroxy‐5, 3′‐dimethoxyflavanonol (4, 4.1 mg), and quercetin (5, 3.8 mg), were successfully obtained from 250 mg of the extracted flavonoids by HSCCC. Conclusion: Results demonstrated that the combination of DES and HSCCC is a powerful technique for the extraction, and isolation of flavonoids from the thorns of G. sinensis compared with conventional organic solvent extraction and column chromatography, which have been proven to provide higher extraction efficiency for flavonoids and rapidly obtain the quality control markers of flavonoids from the investigated plant. Abstract : An efficient method for extraction and separation of flavonoids from the thorns of Gleditsia sinensis was established by choline chloride deep eutectic solvents and high speed counter‐current chromatography. As for extraction, DES composed of choline chloride and 1, 4‐butanediol at 1:4 M ratio, 55oC of extraction temperature, 20% of water content, 1:30 mg/mL for solid‐liquid ratio, and 45 min for extraction time were optimized for flavonoids. As for separation, dichloromethane‐methanol‐n‐butanol‐water (4:3:0.5:2, v/v) was applied to purify five flavonoids by HSCCC.